Pin Duta Literasi (PINDULIT) Sebagai Upaya Peningkatan Gerakan Literasi Sekolah - Khaningrum, Nadia Imti; Rochmiyati, Siti (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
The School Literacy Movement is a government program to create a generation that likes reading books and has life skills, but in its implementation at SD Negeri 3 Kalipetir there are several indicators of the program that have not been implemented well, such as the 15 minute reading activity routine, the low number of students who have notes. Based on these problems, the PINDULIT (Pin Literacy Ambassador) program was implemented. The aim of this research is to determine the increase in student literacy in the GLS program using PINDULIT activities. This research is classroom action research using the Kemmis and Mc Taggart model. The research subjects were 10 class II students. The data collection technique used was observation of the implementation of literacy activities. Data analysis uses quantitative and qualitative descriptive. The results of this research show that the PINDULIT program was said to be successful in increasing student literacy in pre-action activities, the success of program implementation was 60%, then cycle I was 70% and cycle II was 90% in the good category.